2022
DOI: 10.3390/ijms23126658
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Functional Analysis of the bZIP Transcription Factor Family in Rice Bakanae Disease Pathogen, Fusarium fujikuroi

Abstract: Fungal basic leucine zipper (bZIP) proteins play a vital role in biological processes such as growth, biotic/abiotic stress responses, nutrient utilization, and invasion. In this study, genome-wide identification of bZIP genes in the fungus Fusarium fujikuroi, the pathogen of bakanae disease, was carried out. Forty-four genes encoding bZIP transcription factors (TFs) from the genome of F. fujikuroi (FfbZIP) were identified and functionally characterized. Structures, domains, and phylogenetic relationships of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…These TFs function by mediating and regulating the expression of defense-related genes, thereby enhancing plant resistance against pathogen attacks during both PTI and ETI. Previous studies have identified several major TF families, such as WRKY, AP2/ERF, bZIP, bHLH, and MYC, which are involved in plant defense response [ 48 , 49 , 50 , 51 ]. In the current study, we observed a significant upregulation of the RLK, WRKY, AP2/ERF, and MYB families following pathogen infection ( Figure 5 ), suggesting their potential involvement in the response to MR-9 infection.…”
Section: Discussionmentioning
confidence: 99%
“…These TFs function by mediating and regulating the expression of defense-related genes, thereby enhancing plant resistance against pathogen attacks during both PTI and ETI. Previous studies have identified several major TF families, such as WRKY, AP2/ERF, bZIP, bHLH, and MYC, which are involved in plant defense response [ 48 , 49 , 50 , 51 ]. In the current study, we observed a significant upregulation of the RLK, WRKY, AP2/ERF, and MYB families following pathogen infection ( Figure 5 ), suggesting their potential involvement in the response to MR-9 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The VvSTP genes were knocked out using a protocol described in one of our previous publications [ 73 ]. A double-joint PCR method was used to construct the DNA fragments for the genetic recombinant [ 74 ], and the detail was also described in our paper [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…The VvSTP genes were knocked out using a protocol described in one of our previous publications [ 73 ]. A double-joint PCR method was used to construct the DNA fragments for the genetic recombinant [ 74 ], and the detail was also described in our paper [ 73 ]. By using the standard PEG-mediated method [ 75 ], we directly transformed the wild-type strain JZ-11-28, replacing the target VvSTP genes with the hygromycin resistance gene to produce VvSTP gene deletion mutants.…”
Section: Methodsmentioning
confidence: 99%
“…Two domains make up bZIP proteins: a highly conserved DNA-binding basic region and a varied leucine zipper ( 7 ). In pathogenic fungi, the bZIP-type TFs have diverse biological functions related to metabolism, development, reproduction, conidiation, stress responses, and pathogenicity ( 8 10 ). For Metarhizium rileyi ( 11 ), Metarhizium robertsii ( 12 ), and Beauveria bassiana ( 13 ), respectively, the function of bZIP-type TFs in EPF includes vegetative growth, conidia and microsclerotia formation, spore adherence, and virulence via the TF of activator protein 1, bZIP-type TF gene MAA_01736, and HapX.…”
Section: Introductionmentioning
confidence: 99%